Assessment of Self-Nanoemulsifying Drug Delivery System (SNEDDS) of Ethyl Acetate Fraction from Mangosteen (Garcinia mangostana L.,) Peels to Eschericia coli, Pseudomonas aeroginosa, and Proteus mirabilis - Liza Pratiwi (Faculty of Pharmacy, Universitas Gadjah Mada, 2019)
Mangosteen peels have antibacterial activity. SNEDDS has many advantages in developing a drug delivery system to increase the penetration of active compounds. The purpose of this study was to compare the effectiveness of the antibacterial SNEDDS of ethyl acetate fraction from mangosteen peels and ethyl acetate fraction of mangosteen peels without SNEDDS preparation as an antibacterial against Eschericia coli, Pseudomonas aeroginosa, and Proteus mirabilis, that cause diabetic ulcers. This research began with maceration. The thick ethanol extracts were continued and fractionation was carried out with ethyl acetate solvents then was formulated into SNEDDS. The measurement of the antibacterial activity with the bacterial growth inhibition parameters of SNEDDS preparations extracted from ethyl acetate fraction of mangosteen peels was compared with ethyl acetate fraction of mangosteen peels without SNEDDS preparation. Data were analyzed using independent sample T-Test. The results showed the SNEDDS preparation of ethyl acetate fraction from mangosteen peel had activity against both types of bacteria causing diabetic ulcers, but it had no activity against Proteus mirabilis. The results of statistical analysis showed that there were significant differences in the activity of SNEDDS ethyl acetate fraction of mangosteen peels and ethyl acetate fraction of mangosteen peels without SNEDDS in Eschericia coli and Pseudomonas aeruginosa.